2020
DOI: 10.3390/cells9061371
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Abnormalities of Cystic Fibrosis Airway Connective Tissue Revealed by an In Vitro 3D Stromal Model

Abstract: Cystic fibrosis is characterized by lung dysfunction involving mucus hypersecretion, bacterial infections, and inflammatory response. Inflammation triggers pro-fibrotic signals that compromise lung structure and function. At present, several in vitro cystic fibrosis models have been developed to study epithelial dysfunction but none of these focuses on stromal alterations. Here we show a new cystic fibrosis 3D stromal lung model made up of primary fibroblasts embedded in their own extracellular matrix and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…A CF stromal lung model based on fibroblasts from patients with CF found that fibroblasts maintain an activated pro-fibrotic state in vitro and a high proliferation rate. Furthermore, this model showed enhanced pro-fibrotic markers and upregulation of genes involved in epithelial function and inflammatory response [ 57 ]. In patients with COPD, fibroblasts demonstrate decreased capacity for sustaining tissue repair [ 58 ].…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…A CF stromal lung model based on fibroblasts from patients with CF found that fibroblasts maintain an activated pro-fibrotic state in vitro and a high proliferation rate. Furthermore, this model showed enhanced pro-fibrotic markers and upregulation of genes involved in epithelial function and inflammatory response [ 57 ]. In patients with COPD, fibroblasts demonstrate decreased capacity for sustaining tissue repair [ 58 ].…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…Additional cell types, such as pulmonary macrophages and lung fibroblasts, are also missing from the model, and they could be added in the future as well. Indeed, the pathogenetic relevance of the airway connective tissue has been recently documented in a 3D CF stromal lung model [30]. It is possible that the absence of some or all of these CF patient-derived cells could contribute to the explanation of why we did not observe .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 61%
“…In addition, transwell cultures allow the investigation of the interactions among cell and tissue types, pathogens and the immune system [ 30 , 31 , 32 ]. These models have been extensively exploited to study CF, chronic obstructive pulmonary disease (COPD) and airway infections by bacterial and viral pathogens [ 33 , 34 , 35 , 36 ].…”
Section: Lung 3d Culturesmentioning
confidence: 99%